Pengaruh Media Pembelajaran Powerpoint Menggunakan Liquid Crystal Display (LCD) Terhadap Motivasi Dan Minat Belajar Siswa Kelas Xii IPS MA Darul Abidin NW Lendang Ara - Qurratul Aini; Danang Prio Utomo; Muhammad Rapii; Susilawati Susilawati (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
The purpose of this study was to determine how much influence the powerpoint media had on the motivation and interest in learning of class XI IPS MA Darul Abidin NW Lendang Ara. This research was conducted in class XI IPS MA Darul Abidin NW Lendang Ara with a total sample of 27 students studied. The method used in this research is the experimental quantitative research method, with one sample group technique because the researchers only took samples in class XI IPS and did not take other classes. The research results obtained (1) there is a positive and significant influence of powerpoint learning media with student learning motivation because the sig value is 0.00 0.05 so there is a significant effect, and the level of influence is 12%. Whereas for (2) powerpoint media with student interest in learning there is a positive and significant influence and can be proven by a sig value of 0.00 0.05 so that in this variable there is a positive and significant influence, for the level of influence is 9%.